2015
DOI: 10.1063/1.4913637
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and electronic structure of (001)- and (111)-oriented LaTiO3 bilayers sandwiched in LaScO3 barriers

Abstract: Magnetism and electronic structure of (001)-and (111)-oriented LaTiO 3 bilayers sandwiched in LaScO 3 barriers

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
3
1
0
Order By: Relevance
“…In a recent study, we found that the YTiO 3 film on LaAlO 3 becomes A-type antiferromagnetic when growing along the [001]-axis [12], while it retains ferromagnetism when growing along the [110]axis; this finding agrees with experimental observations [13,14]. For LaTiO 3 , the exchange coefficients and, thus, the Neel temperature were predicted to be significantly enhanced in the [111] bilayer compared with the [001] one [15]. In addition, for SrMnO 3 films grown on SrTiO 3 (111) substrates, a hexagonal (4H) structure is more stable than the cubic phase [16].…”
Section: Introductionsupporting
confidence: 86%
“…In a recent study, we found that the YTiO 3 film on LaAlO 3 becomes A-type antiferromagnetic when growing along the [001]-axis [12], while it retains ferromagnetism when growing along the [110]axis; this finding agrees with experimental observations [13,14]. For LaTiO 3 , the exchange coefficients and, thus, the Neel temperature were predicted to be significantly enhanced in the [111] bilayer compared with the [001] one [15]. In addition, for SrMnO 3 films grown on SrTiO 3 (111) substrates, a hexagonal (4H) structure is more stable than the cubic phase [16].…”
Section: Introductionsupporting
confidence: 86%
“…With LDA+U , a Mott-insulator with G-AFM is the ground state, as found in the experiment. The calculated energy gap of 0.25 eV agrees well with the experimental value 0.2 eV [26] and the calculated local magnetic moment is 0.669 µ B /per Ti, slightly larger than the experimental value 0.57 µ B [21] but in agreement with previous DFT results [17].…”
supporting
confidence: 90%
“…For example, LTO and YTO films grown on the compressive [001] LaAlO 3 (LAO) substrate were predicted to show A-type antiferromagnetism (AFM) although their bulks show different original magnetic orders [13,14]. In addition to the substrate constraint (e.g., compressive or tensile), the growth orientation is also important in determining the physical properties of oxide films and superlattices, such as orientation-dependent magnetism and orientationdependent metal-insulator transition [15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…This gap size is larger than the bulk LTO optical gap (∼ 0.2 eV) being consistent with the conductivity data on (LTO) 1,2,3 /(LAO) 5 which reports that the lowest energy excitation is gradually moving toward the higher frequency as the LTO layer thickness is reduced [34]. At a realistic value of U = 3 eV for the superlattice [35,37], the magnetic transition between ferromagnetic (FM-I) and PM-I occurs at T c 12.5meV in good agreement with the total energy difference by GGA+U [35]. Overall, our DMFT results in large-U and low-T limit are consistent with As the more tensile strain applied the bandwidth is gradually decreased as expected.…”
supporting
confidence: 88%